Gender differences in exercise-induced changes in sex hormone levels and lipid peroxidation in athletes participating in the Hawaii Ironman triathlon - Ginsburg, G. S.; O'Toole, M.; Rimm, E.; Douglas, P. S.; Rifai, N. (Clinica Chimica Acta, 2001)
Background: Exercise reduces the risk of coronary heart disease in men and women but paradoxically, may promote free-radical formation, lipid peroxidation and vascular tissue injury. In this study, we assessed whether exercise-induced oxidative stress similarly affected men and women who participated in the Hawaii Ironman triathlon. Methods and results: Fifty-seven athletes (38 males) who completed the triathlon (3.9 km swim, 180.2 km bike, 42.2 km run) participated in this study. Blood samples were obtained 2 days before and immediately after the triathlon for the measurement of lipids, antioxidants and sex hormones and for the assessment of the susceptibility of plasma lipids to peroxidation. Lipid changes after exercise were similar for men and women. However, the susceptibility of plasma lipids to peroxidation was reduced by 61% (P<0.001) in men and only 14% (P=NS) in women postrace. These changes were not associated with the supplemental use or levels of antioxidants. In addition, in men there was an increase of 58% in the antioxidant sex hormone estradiol and a decrease of 58% in testosterone (P<0.001) postrace. No significant changes were noted for these two hormones in women. Conclusions: There are significant gender-specific differences in the susceptibility of lipids to peroxidation and in changes in estradiol and testosterone levels as a result of ultra-endurance exercise. These changes may in part explain the salutary effect of exercise on the development of vascular disease.